Effectiveness of the Application of Drip Irrigation In Some Planting Media for Caisim (Barassica juncea L). - Ikhsan Ali, Muhammad; Suhardi; Haerani (Program Studi Teknik Pertanian Universitas Hasanuddin, 2024)
Caisim plants are cultivated in highland areas. One of the methods to increase the productivity of caisim is by balancing the amount of water supplied and water needs of the plants. This can be done by applying drip irrigation where water was applied to the plants according to their needs. In addition, setting the appropriare composition of planting medium also needs to be done in increasing the productivity of caisim. This study aims to determine the effect of water application and the composition of several planting media in increasing the growth of caisim using drip irrigation. This research used a completely Randomized Disign (CRD) which consisted of two treatment factos, namely provision of water (A) and planting medium (B). The water supply factor consisted of three treatments, i.e AI (2.49 l/day), A2 (2.69 l/day) and A3 (2.89 l/day). The planting media factors consisted of 3 treatments, i.e B1 (soil + cocopeat 2:1), B2 (soil + husk charcoal 2:1) and B3 (soil + manure 2:1). Research data were analyzed using analysis of variance. In case the analyses results in a significant effect, Duncan's New Multiple Range Test (DNMRT) will be performed. The results of the study showed that the application of water at 2.69 l/day and the use of planting media (soil + cow dung manure 2:1) resulted in the best growth and yield of caisim.